Uji Susceptibility Nyamuk Aedes aegypti terhadap Insektisida Malathion di Wilayah Fogging Kabupaten Malang - Zada Alimatul Mu’azah; Ainur Rofieq; Mohammad Mirza Nuryady; Tutut Indria Permana; Anka Mohammad Dinindra; Jihan Ully Agustin; Nur Ilmi Dwi Sasmitasari; Muhammad Ahman Luthfi Setiawan; Putri Ayu Irrodah (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Malang Regency is an endemic area for cases of DHF (Dengue Hemorrhagic Fever) in East Java Province. One of the efforts to reduce the number of cases is to control the breeding of the Aedes aegypti mosquito which is the main vector. However, this will depend on the susceptibility status of Aedes aegypti to the insecticides used, one of which is malathion. This study aims to determine the susceptibility status of Aedes aegypti mosquitoes to malathion insecticides in Malang Regency in the southern part. This descriptive observational study used adult Aedes aegypti mosquitoes obtained from the landing collection of larvae from three sub-districts in Malang Regency in the southern part (Kepanjen, Gondanglegi, and Bantur). The location selection was done by simple random sampling technique. The larvae of the Aedes aegypti mosquito were then reared in the Chemistry Laboratory, University of Muhammadiyah Malang. Adult mosquitoes with stomach conditions full of sugar were then tested using the susceptibility test which refers to WHO standards. The results showed that the mortality rate of the tested mosquitoes in the Districts of Kepanjen, Gondanglegi, and Bantur, respectively, reached 98%, 93%, and 96%. This shows that the Aedes aegypti mosquitoes in the three locations are classified as tolerant to the insecticide malathion by 0.8%. Thus, it can be concluded that the insecticide malathion is still effectively used as vector control for DHF (Dengue Hemorrhagic Fever) in Malang Regency.